ONLINE SENSOR COLLABORATION TO ACHIEVE QUALITY OF SERVICE REQUIREMENTS IN WIRELESS SENSOR NETWORKS (Global Journals of Research in Engineering, 2011)
Wireless Sensor networks are currently being employed in a variety of applications ranging from medical to military, and from home to industry. Wireless Sensor Networks and Applications aims to provide a reference tool for the increasing number of scientists who depend upon reliable sensor networks. A fundamental challenge for these wireless sensor networks is to meet stringent Quality-of-Service requirements including high target detection probability, low false alarm rate, and bounded detection delay. This paper present a new formulation for the problem of target detection based on a novel two-phase detection approach .A near-optimal movement scheduling algorithm is developed that minimizes the expected moving distance of mobile sensors . It exploits reactive mobility to improve the target detection performance of moving targets in wireless sensor networks. In this approach, mobile sensors collaborate with static sensors and move reactively to achieve the required detection performance. Specifically, mobile sensors initially remain stationary and are directed to move toward a possible target only when a detection consensus is reached by a group of sensors.